Perancangan Iklan Sosial “Kali Resik, Solo Apik” Menyadarkan Arti Sungai Bersih Bagi Masyarakat Kota Surakarta - Charles Sari Charles Yordan; Basnendar Herry Prilosadoso (CITRAWIRA : Journal of Advertising and Visual Communication, 2021)
Through a social advertisement or campaign, it is expected to be able to make people care more about the surrounding environment. One of them is more concerned about the river where now many rivers are affected by pollution. The concept of social advertising through a comprehensive campaign strategy through various media (Integrated Advertising Campaign). This design also uses a visual communication method approach based on existing facts, namely the problem of river pollution which has quite an impact on the river ecosystem environment. An important keyword as a slogan is "Kali Resik, Solo Apik” is a strategy to approach community participation to further strengthen campaign activities so that the message to be conveyed can be understood by the entire community. This social advertising campaign is not only aimed at the people of the riverbanks or riverbanks, but also all levels of society in the city of Surakarta.